Volume 3: Turbo Expo 2005, Parts a and B 2005
DOI: 10.1115/gt2005-68598
|View full text |Cite
|
Sign up to set email alerts
|

Film Cooling From a Row of Holes Embedded in Transverse Slots

Abstract: Film cooling performance for a row of cylindrical holes can be enhanced by embedding the row in transverse slots. The geometry of the transverse slot greatly affects the cooling performance downstream of injection. The effect of the slot exit area and edge shape is investigated. Detailed heat transfer coefficient and film effectiveness measurements are obtained simultaneously using a single test transient IR thermography technique. The study is performed at a single mainstream Reynolds number based on free-str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Certain configurations of cylindrical holes embedded in transverse trenches have been shown to perform similarly to shaped holes, and trenches would be cheaper to manufacture than shaped holes. Several studies have investigated various trench configurations such as Bunker [14], Waye and Bogard [15], Lu et al [16], Harrison and Bogard [17], Jia et al [18], Zuniga and Kapat [19].…”
Section: A Review Of Studies On Film Cooling Effectivenessmentioning
confidence: 99%
“…Certain configurations of cylindrical holes embedded in transverse trenches have been shown to perform similarly to shaped holes, and trenches would be cheaper to manufacture than shaped holes. Several studies have investigated various trench configurations such as Bunker [14], Waye and Bogard [15], Lu et al [16], Harrison and Bogard [17], Jia et al [18], Zuniga and Kapat [19].…”
Section: A Review Of Studies On Film Cooling Effectivenessmentioning
confidence: 99%
“…Results showed the radial angle shaped hole. Lu et al (2005) investigated the film cooling performance for a row of cylindrical holes by embedding the row in transverse slots. Transverse slots could be formed around the holes in the event that the blade surface is sprayed with TBC leaving the holes embedded in trenches.…”
Section: Work In 1990smentioning
confidence: 99%
“…Due to the depth under the surface, the coolant jet may be attached to the surface under the higher blowing ratio. Lu (Lu et al, 2005) found that the trench depth of 0.75D was optimum. Dorrington (Dorrington et al, 2007) investigated the trench width and found that the narrow trench performed better film-cooling effectiveness at shallow trench.…”
Section: Introductionmentioning
confidence: 98%